2019
DOI: 10.1136/vr.105131
|View full text |Cite
|
Sign up to set email alerts
|

Placebo‐controlled study on the effects of oral administration ofAllium sativumL in postweaning piglets

Abstract: Postweaning diarrhoea (PWD) due to Escherichia coli is an economically important disease in pig production. In this placebo-controlled study performed in Switzerland, the effects of oral supplementation of Allium sativum L. (garlic, AS) on performance (bodyweight (BW) and daily weight gain (DWG)) and health (body condition and clinical score) were investigated in postweaning piglets. Piglets (n=600) were randomly assigned to the treatment groups (placebo, AS or colistin) and observed from birth until three wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
0
4
0
3
Order By: Relevance
“…The results of the study revealed that the piglets that received garlic supplementation had an increased growth performance and an improved clinical health score. However, the desired reduction of the incidence and severity of postweaning diarrhoea did not occur 7 …”
Section: Common Name Latin Name Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations
“…The results of the study revealed that the piglets that received garlic supplementation had an increased growth performance and an improved clinical health score. However, the desired reduction of the incidence and severity of postweaning diarrhoea did not occur 7 …”
Section: Common Name Latin Name Characteristicsmentioning
confidence: 98%
“…5,6 In a study summarised on p 316 of this issue of Vet Record, Ayrle and colleagues evaluated the efect of oral garlic supplementation on certain performance (bodyweight and daily weight gain) and health (body condition and clinical score) variables in postweaning pigs in Switzerland. 7 It was hypothesised that garlic supplementation would reduce the incidence and severity of postweaning diarrhoea. The study was conducted at a conventional piglet-producing farm in Switzerland (Fig 1).…”
Section: Medicinal Plants -An Underestimated Option To Treat Gastroinmentioning
confidence: 99%
See 1 more Smart Citation
“…Weitere 7 Tage später lagen bei andauernder und an das zunehmende Körpergewicht angepasster Dosierung die E. coli-CFU bereits schon wieder 100fach höher bei ca. 10 5 [2]. Hätte man mit einer noch höheren Dosierung noch mehr bewirkt?…”
unclassified
“…In der Folge, nicht zuletzt auch bedingt durch den abrupten Futterwechsel, entwickeln Ferkel den sogenannten "Absetzerferkeldurchfall". In einem randomisierten, placebokontrollierten, monozentrischen klinischen Feldversuch wurde die Wirkung der Gabe von 0,3g Knoblauch pro kg Körpergewicht Ferkel und Tag mit der Gabe von 6 mg Colistinsulfat verglichen[2].Auf eine Verblindung wurde in dieser dreiarmigen Studie bewusst verzichtet, stellt sich doch die olfaktorische Verblindung von Knoblauch als schier unmöglich dar (die sich für einige Zeit im Büro des (eher riechschwachen) Erstautors befindliche -wohlbemerkt in der Originalverpackung verpackte und zusätzlich in einem Schraubdeckelglas verschraubte -Rückstellprobe des Knoblauchpulvers pharmazeutischer Qualität machte sich innert kürzester Zeit olfaktorisch derart bemerkbar, dass sie des Raumes verwiesen werden musste). Die Ferkel einer Sau wurden bereits innerhalb der ersten 72 Lebensstunden zufällig auf die 3 Behandlungsgruppen verteilt.…”
unclassified